NMR Spectra Particularities in LiNbO3 Crystals with a Near-Stoichiometric Composition - Alexander Yatsenko; Sergey Yevdokimov; Mikhail Palatnikov; Nikolay Sidorov (Ceramics, 2023)
The paper studies LiNbO3 (LN) crystals with a near-stoichiometric composition (NSLN). The study establishes the possibility of different physical methods to reveal NSLN crystals’ exact composition. The main goal was to establish how precisely these methods can reveal a NSLN composition, including a defective structure. This structure determines properties that are important for the application of the crystals. Two NSLN crystals with a different Li/Nb ratio have been studied by IR and NMR spectroscopy. NSLN crystals have been grown from a congruent melt with different K2O flux contents (5.0 and 5.5 wt%). The data on NSLN have been compared with the data on congruent (CLN) crystals. CLN are the most widely used LN crystals. The study has established that analysis of the IR spectra can determine the Li/Nb ratio within [Li2O] = 48.6 – 50.0 mol% range, while the 93Nb NMR spectra has a wider range of sensibility. LN crystals’ stoichiometry or the Li/Nb ratio determine the concentration of antisite defects NbLi. Niobium substitutes lithium in its octahedron. Such defects appear up to [Li2O] = 49.9 mol%. Thus, the study shows that IR and NMR spectroscopy are sensitive methods that can complement each other when determining the precise LN composition (Li/Nb ratio) and the presence of intrinsic defects in the crystals.